Polarizing film, image display device, and method for producing polarizing film

JP7610581B2Active Publication Date: 2025-01-08NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022509338
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-02-01
Publication Date
2025-01-08
Estimated Expiration
2041-02-01

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、高温多湿環境下において、偏光子に含まれるヨウ素の外部への透過を十分に抑制することができる偏光フィルムを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610581000002
    Figure 0007610581000002
  • Figure 0007610581000003
    Figure 0007610581000003
  • Figure 0007610581000004
    Figure 0007610581000004
Patent Text Reader

Abstract

The present invention provides a polarization film capable of suppressing sufficiently the outward permeation of iodine contained in a polarizer under a high-temperature and high-humidity environment. This polarization film comprises a polarizer containing iodine, and a resin layer containing a polymer having a structure unit derived from a (meth)acrylic acid ester. In the polarization film, the value of y1 as calculated from formula (1) is less than 1.3. (1): y1 = (0.279) x1 + (-1.51) x2 + (0.178) x3 + 0.386 In formula (1), x1 represents the number of rotatable bonds contained in a monomer for forming the polymer, x2 represents the number of reactive sites contained in the monomer, and x3 represents a polar term δP (MPa1 / 2) in the Hansen solubility parameters for the monomer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing film, an image display device, and a method for producing a polarizing film. [Background technology]

[0002] Image display devices such as liquid crystal display devices and organic EL display devices are provided with a polarizing film for reasons such as their display principles. The polarizing film is, for example, a laminate including a polarizer and a transparent protective film. A polarizer can generally be produced by adsorbing a dichroic dye to a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film and uniaxially stretching the film. From the viewpoint of improving the transmittance and polarization degree of the polarizer, iodine is widely used as the dichroic dye.

[0003] Patent Document 1 discloses an optical laminate in which a polarizer and a protective film are bonded via a cured layer of a curable resin composition. It can be seen from Patent Document 1 that the iodine content in the cured layer can be kept low even when the optical laminate is placed in a high-temperature and high-humidity environment by appropriately adjusting the content of the alicyclic epoxy compound in the curable resin composition. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-169512 A Summary of the Invention [Problem to be solved by the invention]

[0005] In a high-temperature and high-humidity environment, iodine contained in the polarizer tends to migrate from the polarizer to the transparent protective film or the adhesive layer for bonding the polarizing film to the image display panel. In particular, when the thickness of the polarizer is small and the concentration of iodine in the polarizer is high, iodine is likely to migrate from the polarizer to the transparent protective film or the adhesive layer. The iodine that has migrated to the transparent protective film or the adhesive layer is transmitted to the outside of the polarizing film through the transparent protective film or the adhesive layer. When the content of iodine in the polarizer decreases, the polarization degree of the polarizing film decreases.

[0006] Conventional polarizing films cannot sufficiently prevent iodine contained in a polarizer from penetrating to the outside of the polarizing film in a high-temperature and high-humidity environment. For example, Patent Document 1 focuses on maintaining a low iodine content in the cured layer when the optical laminate is placed in a high-temperature and high-humidity environment. However, Patent Document 1 does not take into consideration the penetrating of iodine from the polarizer to the outside of the optical laminate.

[0007] Therefore, an object of the present invention is to provide a polarizing film that can sufficiently suppress the transmission of iodine contained in a polarizer to the outside in a high-temperature and high-humidity environment. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have newly found that the properties of a resin layer included in a polarizing film can be predicted based on a monomer for forming a polymer contained in the resin layer. According to the research of the present inventors, this prediction is particularly reliable for a resin layer containing a polymer having a structural unit derived from a (meth)acrylic acid ester. Based on this finding, the present inventors have further researched and have completed the present invention.

[0009] The present invention relates to a polarizer including iodine; a resin layer containing a polymer having a structural unit derived from a (meth)acrylic acid ester, The present invention provides a polarizing film having a value of y1 calculated by the following formula (1) of less than 1.3. y1=(0.279)x1+(-1.51)x2+(0.178)x3+0.386 (1) In the formula (1), x1 is the number of rotatable bonds contained in the monomer for forming the polymer, x2 is the number of reaction sites contained in the monomer for forming the polymer, x3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ).

[0010] Further, the present invention relates to A method for producing a polarizing film including an iodine-containing polarizer and a resin layer including a polymer having a structural unit derived from a (meth)acrylic acid ester, comprising: The manufacturing method includes: The present invention provides a method for producing a polarizing film, comprising the step of polymerizing a monomer having a value of y1, calculated by the following formula (1), of less than 1.3, to obtain the polymer. y1=(0.279)x1+(-1.51)x2+(0.178)x3+0.386 (1) In the formula (1), x1 is the number of rotatable bonds contained in the monomer, x2 is the number of reactive sites contained in the monomer, x3 is the polarization term δP (MPa 1 / 2 ).

[0011] Further, the present invention relates to a polarizer including iodine; a resin layer containing a polymer having a structural unit derived from a (meth)acrylic acid ester, The present invention provides a polarizing film having a value of y2 calculated by the following formula (2) of less than 1.3. y2=(0.255)x1+(-1.57)x2+(0.151)x3+(-18.0)x4+(0.0987)x5+(-8.26) (2) In the formula (2), x1 is the number of rotatable bonds contained in the monomer for forming the polymer, x2 is the number of reaction sites contained in the monomer for forming the polymer, x3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ) and x4 is the charge (C) of the most negatively charged atom among the atoms functioning as a hydrogen bond acceptor in the monomer for forming the polymer, x5 is the x component (Debye) of the dipole moment of the monomer that forms the polymer.

[0012] Further, the present invention relates to A method for producing a polarizing film including an iodine-containing polarizer and a resin layer including a polymer having a structural unit derived from a (meth)acrylic acid ester, comprising: The manufacturing method includes: The present invention provides a method for producing a polarizing film, comprising the step of polymerizing a monomer having a value of y2, calculated by the following formula (2), of less than 1.3, to obtain the polymer: y2=(0.255)x1+(-1.57)x2+(0.151)x3+(-18.0)x4+(0.0987)x5+(-8.26) (2) In the formula (2), x1 is the number of rotatable bonds contained in the monomer for forming the polymer, x2 is the number of reaction sites contained in the monomer for forming the polymer, x3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ) and x4 is the charge (C) of the most negatively charged atom among the atoms functioning as a hydrogen bond acceptor in the monomer for forming the polymer, x5 is the x component (Debye) of the dipole moment of the monomer that forms the polymer. Effect of the Invention

[0013] According to the present invention, it is possible to provide a polarizing film capable of sufficiently suppressing the transmission of iodine contained in a polarizer to the outside in a high-temperature and high-humidity environment. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view of a polarizing film according to one embodiment of the present invention. [Diagram 2] FIG. 11 is a schematic cross-sectional view showing a modified example of the polarizing film. [Diagram 3] FIG. 11 is a schematic cross-sectional view showing another modified example of the polarizing film. [Figure 4] FIG. 11 is a schematic cross-sectional view showing still another modified example of the polarizing film. [Diagram 5] 1 is a schematic cross-sectional view of an image display device according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described in detail, but the following description is not intended to limit the present invention to a specific embodiment.

[0016] (Embodiments of Polarizing Film) As shown in FIG. 1, the polarizing film 10 of the present embodiment includes a polarizer 1 containing iodine and a resin layer 2 containing a polymer P. The polymer P contained in the resin layer 2 has a structural unit derived from a (meth)acrylic acid ester. In this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid. The resin layer 2 is located, for example, on the viewing side of the polarizer 1 and is in direct contact with the polarizer 1. However, other layers such as an adhesive layer and an easy-adhesion layer may be disposed between the resin layer 2 and the polarizer 1 as long as they do not impede the effects of the present invention. The resin layer 2 may be located closer to an image display panel, which will be described later, than the polarizer 1. In other words, the polarizer 1 may be located on the viewing side of the resin layer 2. The resin layer 2 is located, for example, on the outermost side of the polarizing film 10. In this specification, the term "film" refers to a member having a thickness sufficiently smaller than its length and width.

[0017] The polarizing film 10 may further include an adhesive layer 3, a transparent protective film (first transparent protective film) 4, and a pressure-sensitive adhesive layer 5. The transparent protective film 4 is attached to the polarizer 1, for example, via the adhesive layer 3. The pressure-sensitive adhesive layer 5 functions as a member for attaching the polarizing film 10 to an image display panel, which will be described later, for example. Therefore, the pressure-sensitive adhesive layer 5 is, for example, located on the outermost side of the polarizing film 10, closer to the image display panel than the polarizer 1. In other words, the polarizer 1 is, for example, located on the viewing side than the pressure-sensitive adhesive layer 5. The resin layer 2, the polarizer 1, the adhesive layer 3, the transparent protective film 4, and the pressure-sensitive adhesive layer 5 are, for example, arranged in this order in the stacking direction.

[0018] In the polarizing film 10 of this embodiment, the value of y1 calculated by the following formula (1) is less than 1.3. y1=(0.279)x1+(-1.51)x2+(0.178)x3+0.386 (1)

[0019] In formula (1), x1 is the number of rotatable bonds contained in the monomer M for forming the polymer P. x1 can be an index for predicting the degree to which the molecular motion of the polymer P is restricted. In this specification, the term "rotatable bond" refers to a single bond between heavy atoms, excluding a single bond contained in a ring structure and a single bond between a heavy atom located at an end and another heavy atom. The heavy atom refers to an atom other than a hydrogen atom and a helium atom, and specifically includes a heteroatom such as a nitrogen atom or an oxygen atom, and a carbon atom. Specific examples of single bonds between heavy atoms are a carbon-carbon bond and a carbon-heteroatom bond. As an example, when the polymer P is formed from dimethylol-tricyclodecane diacrylate, the value of x1 is 8. The number of rotatable bonds may be calculated using software for calculating molecular descriptors. Examples of such software include Dragon (version 7.0) and alvaDesc.

[0020] When the polymer P is formed from multiple types of monomers M, the value of x1 can be specified by the following method. First, the number of rotatable bonds is calculated for each of the multiple types of monomers M. The calculated numbers of rotatable bonds are weighted by the molar ratio of each monomer M to obtain a weighted average. The obtained weighted average value can be regarded as x1. In this embodiment, the value of x1 is not particularly limited and is, for example, 2 to 20.

[0021] x2 is the number of reactive sites contained in the monomer M for forming the polymer P. x2 can be an index for predicting the degree to which gaps large enough for a low molecular weight compound to pass through are present in the polymer P. In this specification, the term "reactive site" means a polymerizable group or a crosslinkable group. Specific examples of these groups include groups having a polymerizable double bond such as a (meth)acryloyl group, and crosslinkable functional groups such as an epoxy group and an oxetane group. As an example, when the polymer P is formed from dimethylol-tricyclodecane diacrylate, the value of x2 is 2. The number of reactive sites may be calculated using the software for calculating the molecular descriptors described above.

[0022] When the polymer P is formed from multiple types of monomers M, the value of x2 can be specified by the following method. First, the number of reaction sites is calculated for each of the multiple types of monomers M. The calculated number of reaction sites is weighted by the molar ratio of each monomer M to obtain a weighted average. The obtained weighted average value can be regarded as x2. In this embodiment, the value of x2 is not particularly limited and is, for example, 1 to 6.

[0023] x3 is the polarization term δP (MPa) in the Hansen solubility parameter of monomer M to form polymer P 1 / 2 ) x3 can be an index for predicting the interaction between the polymer P and water molecules or iodine. The Hansen solubility parameter is a solubility parameter introduced by Hildebrand divided into three components: a dispersion term δD, a polarization term δP, and a hydrogen bond term δH. The polarization term δP indicates the energy due to the dipole interaction between molecules. Details of the Hansen solubility parameter are disclosed in "Hansen Solubility Parameters; A Users Handbook (CRC Press, 2007)". The polarization term δP can be calculated using known software such as HSPiP (version 5). The value of the polarization term δP may vary slightly depending on the software used. However, this error is usually negligible when calculating the value of y1.

[0024] When the polymer P is formed from multiple types of monomers M, the value of x3 can be determined by the following method. First, for each of the multiple types of monomers M, the polarization term ΔP (MPa 1 / 2 ) is calculated. The calculated polarization term ΔP is weighted by the molar ratio of each monomer M to obtain a weighted average. The weighted average value obtained can be regarded as x3. In this embodiment, the value of x3 is not particularly limited, and may be, for example, 1 to 10 (MPa 1 / 2 ). The value of x3 is preferably 6 (MPa1 / 2 ) or less, more preferably 5 (MPa 1 / 2 ) or less, and more preferably 4 (MPa 1 / 2 ) or less.

[0025] In the polarizing film 10 of this embodiment, the value of y2 calculated by the following formula (2) may be less than 1.3. y2=(0.255)x1+(-1.57)x2+(0.151)x3+(-18.0)x4+(0.0987)x5+(-8.26) (2)

[0026] From another aspect, the present invention provides a polarizing film 10 comprising a polarizer 1 containing iodine and a resin layer 2 containing a polymer P having a structural unit derived from a (meth)acrylic acid ester, wherein the value of y2 calculated by formula (2) is less than 1.3.

[0027] In formula (2), x1 to x3 are the same as in formula (1). Therefore, the method of specifying x1 to x3 in formula (2) is the same as that described above.

[0028] In formula (2), x4 is the charge (C) of the most negatively charged atom among the atoms that function as hydrogen bond acceptors in the monomer M for forming the polymer P. x4 can be an index for predicting the interaction that occurs between the polymer P and water molecules, that is, an index for predicting the degree of hydrophobicity of the polymer P. The closer the value of x4 is to 0, the more hydrophobic the polymer P tends to be. A hydrogen bond acceptor refers to an atom that can form a hydrogen bond with a hydrogen atom contained in a water molecule. Atoms that function as hydrogen bond acceptors include atoms with relatively high electronegativity, such as oxygen atoms and nitrogen atoms.

[0029] x4 can be specified, for example, by the following method. First, a monomer M for forming a polymer P is specified. By performing a molecular simulation on the monomer M, the charge (Mulliken charge) of each atom constituting the monomer M can be calculated. The molecular simulation can be performed using known software such as Materials Studio (manufactured by BIOVIA, ver. 8.0.0.843) and WebMO (ver. 19.0.009e).

[0030] The molecular simulation can be performed, for example, by the following method. First, a molecular model of monomer M is created using Materials Studio. The molecular model is optimized in structure by adopting the force field of COMPASS (Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies) II. Next, the molecular model of monomer M is processed by WebMO. In detail, a structure optimization calculation is performed on the molecular model of monomer M using the Gaussian program (Queue: g09) in WebMO. At this time, B3LYP may be used as the functional, and 6-31G(d) may be used as the basis function. The charge of each atom constituting monomer M can be calculated by the above molecular simulation.

[0031] Next, among the atoms constituting the monomer M, an atom that functions as a hydrogen bond acceptor is identified. Furthermore, from among the identified atoms, the most negatively charged atom (an atom that has a negative charge and has the largest absolute value of the charge) is identified. The charge (C) of this atom can be regarded as x4. Note that, if the monomer M does not have an atom that functions as a hydrogen bond acceptor, x4 can be regarded as 0.

[0032] When the polymer P is formed from a plurality of types of monomers M, x4 can be specified by the following method. First, for each of the plurality of types of monomers M, the charge (C) of the most negatively charged atom among the atoms that function as hydrogen bond acceptors is specified by the above-mentioned method. The specified charges are weighted by the molar ratio of each monomer M to obtain a weighted average. The obtained weighted average value can be regarded as x4. Even when the plurality of types of monomers M are structural isomers, x4 can be specified by weighting the specified charges by the molar ratio of each structural isomer to obtain a weighted average. In this embodiment, the value of x4 is not particularly limited, and is, for example, -0.55 to -0.45C.

[0033] x5 is the x component (Debye) of the dipole moment of the monomer M for forming the polymer P. x5 can be an index for predicting the interaction between the polymer P and water molecules, that is, an index for predicting the degree of hydrophobicity and humidification durability of the polymer P. The closer the value of x5 is to 0, the smaller the dipole moment of the monomer M and the more hydrophobic the polymer P tends to be.

[0034] For example, x5 can be specified by the following method. First, a monomer M for forming the polymer P is specified. The x component of the dipole moment can be calculated by performing a molecular simulation on the monomer M. The molecular simulation can be performed by the method described above for x4. When performing the molecular simulation, the internal coordinates of each atom constituting the monomer M are defined by the Z-matrix format. When the Z-matrix format is used, the x-axis, y-axis, and z-axis for determining the internal coordinates are automatically determined according to the structure of the monomer M. The dipole moment is a vector quantity calculated from the x-component, y-component, and z-component.

[0035] When the polymer P is formed from a plurality of types of monomers M, x5 can be specified by the following method. First, the x component in the dipole moment is calculated for each of the plurality of types of monomers M by the above-mentioned method. The x component in the calculated dipole moment is weighted by the molar ratio of each monomer M to obtain a weighted average. The obtained weighted average value can be regarded as x5. Even when the plurality of types of monomers M are structural isomers, x5 can be specified by weighting the x component in the calculated dipole moment by the molar ratio of each structural isomer to obtain a weighted average. In this embodiment, the value of x5 is not particularly limited, and is, for example, -2.0 to 5.0 Debye. The value of x5 may be 3.0 Debye or less, or 1.0 Debye or less.

[0036] The value of y1 calculated by formula (1) and the value of y2 calculated by formula (2) are preferably 0.8 or less, more preferably 0.7 or less, even more preferably 0.5 or less, and particularly preferably 0.3 or less.

[0037] The value of y1 calculated by formula (1) and the value of y2 calculated by formula (2) are indices related to the monomer M for forming the polymer P contained in the resin layer 2. However, according to the studies of the present inventors, the values ​​of y1 and y2 are also useful as indices for selecting a resin layer 2 suitable for suppressing the transmission of iodine contained in the polarizer 1 to the outside. The number of factors (x1 to x5) for calculating y2 is greater than the number of factors (x1 to x3) for calculating y1. In general, the number of factors tends to affect the prediction performance of the prediction formula.

[0038] In the polarizing film 10 of the present embodiment, for example, at least one of the following requirements (i) to (v) is satisfied, and preferably requirement (iii) is satisfied. In the polarizing film 10, all of requirements (i) to (v) may be satisfied. (i) The tensile storage modulus E1 of the resin layer 2 at 65° C. in water is 1×10 8 Pa or more. (ii) The tensile storage modulus E2 of the resin layer 2 at 85°C in water is 1 × 10 8 Pa or more. (iii) The linear expansion coefficient α1 of the resin layer 2 when the resin layer 2 is heated from 25° C. to 65° C. and the measurement atmosphere is humidified from 10% RH to 90% RH is 400×10 -6 / K or less. (iv) The linear expansion coefficient α2 of the resin layer 2 when the resin layer 2 is heated from 25° C. to 85° C. and the measurement atmosphere is further humidified from 10% RH to 85% RH is 300×10 -6 / K or less. (v) The dipole moment D of the monomer M for forming the polymer P contained in the resin layer 2 is 2 Debye or less.

[0039] First, the requirement (i) will be described. The tensile storage modulus E1 of the resin layer 2 is preferably 5×10 8 Pa or more, more preferably 10×10 8 Pa or more, and more preferably 15×10 8 The upper limit of the tensile storage modulus E1 is not particularly limited, but from the viewpoint of suppressing cracks in the resin layer 2, it is, for example, 100×10 8 It may be Pa.

[0040] The tensile storage modulus E1 of the resin layer 2 can be measured, for example, by the following method. First, the resin layer 2 to be evaluated is cut into a strip of 5 mm width and 30 mm length to prepare a test piece. Next, the test piece is set in a commercially available dynamic viscoelasticity measuring device. At this time, a tool capable of immersing the test piece in a solvent is used. The distance between the clamps that fix the test piece is set to 15 mm. Next, the test piece is immersed in water. After confirming that the temperature of the test piece is 25°C, the measurement of the dynamic viscoelasticity of the test piece is started. The measurement is performed by the tensile vibration-non-resonance method specified in Japanese Industrial Standards (JIS) K7244-4:1999. The frequency of vibration is set to 1 Hz. After starting the measurement, the test piece is heated to 95°C at a heating rate of 5°C / min. The measured value of the tensile storage modulus when the temperature of the test piece is 65°C can be regarded as the tensile storage modulus E1 of the resin layer 2.

[0041] Next, the requirement (ii) will be described. The tensile storage modulus E2 of the resin layer 2 is preferably 5×10 8 Pa or more, more preferably 10×10 8 Pa or more, and more preferably 15×10 8 The upper limit of the tensile storage modulus E2 is, but is not particularly limited to, for example, 100×10 8 The tensile storage modulus E2 of the resin layer 2 may be, for example, in units of Pa. The tensile storage modulus E2 of the resin layer 2 can be measured, for example, by the same method as that for the tensile storage modulus E1. In detail, the dynamic viscoelasticity of the test piece is measured by the method described above for the tensile storage modulus E1, and the measured value of the tensile storage modulus when the temperature of the test piece is 85° C. can be regarded as the tensile storage modulus E2 of the resin layer 2.

[0042] Next, the requirement (iii) will be described. The linear expansion coefficient α1 of the resin layer 2 is preferably 200×10 -6 / K or less, more preferably 180×10 -6 / K or less, and more preferably 150×10 -6 / K or less, and particularly preferably 120×10 -6 / K or less. The lower limit of the linear expansion coefficient α1 is not particularly limited, but from the viewpoint of suppressing cracks in the resin layer 2, it is, for example, 10×10 -6 / K may also be used.

[0043] The linear expansion coefficient α1 of the resin layer 2 can be measured, for example, by the following method. First, the resin layer 2 to be evaluated is cut into a strip of 5 mm width and 30 mm length to prepare a test piece. Next, the test piece is set in a commercially available thermomechanical analyzer. At this time, the distance between the clamps fixing the test piece is set to 15 mm. The test piece is left in a measurement atmosphere of 25°C and 10% RH for at least 10 minutes. Next, the test piece is heated to 65°C over 60 minutes, and the test piece is held for 10 minutes. Next, the measurement atmosphere is humidified from 10% RH to 90% RH over 30 minutes, and the test piece is held for 10 minutes. Based on the change in length of the test piece before and after the test, ΔL (mm), the linear expansion coefficient α calculated from the following formula (3) can be regarded as the linear expansion coefficient α1 of the resin layer 2. In addition, in formula (3), L0 means the length of the test piece at 25°C, and ΔT means the change in temperature of the test piece before and after the test. In requirement (iii), ΔT is 40° C. Linear expansion coefficient α = ΔL / (L0 × ΔT) (3)

[0044] Next, the requirement (iv) will be described. The linear expansion coefficient α2 of the resin layer 2 is preferably 200×10 -6 / K or less, more preferably 170×10 -6 / K or less, and more preferably 150×10 -6 / K or less, and particularly preferably 100×10 -6 / K or less. The lower limit of the linear expansion coefficient α2 is not particularly limited, but from the viewpoint of suppressing cracks in the resin layer 2, it is, for example, 10×10 -6 / K. The linear expansion coefficient α2 of the resin layer 2 can be measured by the same method as the linear expansion coefficient α1, except that the test piece is heated to 85°C over 60 minutes and the measurement atmosphere is humidified from 10% RH to 85% RH over 30 minutes. In the requirement (iv), ΔT in the above formula (3) is 60°C.

[0045] Next, the requirement (v) will be described. The dipole moment D of the monomer M for forming the polymer P is preferably 1.7 Debye or less, more preferably 1.5 Debye or less, and further preferably 1.3 Debye or less. The lower limit of the dipole moment D is not particularly limited, and is, for example, 0.5 Debye.

[0046] The dipole moment D can be calculated, for example, by the following method. First, a monomer M for forming a polymer P is identified. The dipole moment D can be calculated by performing a molecular simulation on the monomer M. The molecular simulation can be performed using known software such as Materials Studio (manufactured by BIOVIA, ver. 8.0.0.843) and WebMO (ver. 19.0.009e).

[0047] The calculation of the dipole moment D by molecular simulation can be performed, for example, by the following method. First, a molecular model of the monomer M is created using Materials Studio. For the molecular model, the force field of COMPASS (Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies) II is adopted to optimize the structure. Next, the molecular model of the monomer M is processed by WebMO. In detail, in WebMO, a structure optimization calculation is performed on the molecular model of the monomer M using the Gaussian program (Queue: g09). At this time, B3LYP may be used as the functional, and 6-31G(d) may be used as the basis function. This makes it possible to calculate the dipole moment D of the monomer M.

[0048] When the polymer P is formed from multiple types of monomers M, the dipole moment D can be determined by the following method. First, the dipole moment is calculated for each of the multiple types of monomers M by the above-mentioned method. The calculated dipole moments are weighted by the molar ratio of each monomer M to obtain a weighted average. The obtained weighted average value can be regarded as the dipole moment D. Even when the multiple types of monomers M are structural isomers, the dipole moment D can be calculated by weighting the calculated dipole moments by the molar ratio of each structural isomer to obtain a weighted average.

[0049] When at least one of the requirements (i) and (ii) is satisfied, the polymer P contained in the resin layer 2 tends to maintain a low molecular mobility even in a high-temperature and high-humidity environment. When the molecular mobility of the polymer P is low, spaces into which iodine can enter are unlikely to be generated in the resin layer 2. This tends to suppress the migration of iodine from the polarizer 1 to the resin layer 2, and to suppress the transmission of iodine to the outside of the polarizing film 10.

[0050] When at least one of the requirements (iii) and (iv) is satisfied, the polymer P contained in the resin layer 2 tends to maintain a small free volume even in a high-temperature and high-humidity environment. When the free volume of the polymer P is small, spaces into which iodine can enter are unlikely to be generated in the resin layer 2. This tends to suppress the migration of iodine from the polarizer 1 to the resin layer 2, and to suppress the transmission of iodine to the outside of the polarizing film 10.

[0051] When the requirement (v) is met, electrostatic interaction between the polymer P and iodine tends not to occur easily. In other words, iodine is not easily attracted to the polymer P. This tends to suppress the migration of iodine from the polarizer 1 to the resin layer 2, and to suppress the transmission of iodine to the outside of the polarizing film 10.

[0052] [Polarizer] The polarizer 1 is not particularly limited as long as it contains iodine, and examples thereof include a hydrophilic polymer film, such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, or an ethylene-vinyl acetate copolymer partially saponified film, which is made by adsorbing iodine and uniaxially stretching the film. The polarizer 1 is preferably composed of a polyvinyl alcohol film and iodine.

[0053] The thickness of the polarizer 1 is not particularly limited, and is, for example, 30 μm or less, preferably 20 μm or less, more preferably 18 μm or less, further preferably 15 μm or less, particularly preferably 12 μm or less, and particularly preferably 10 μm or less. The thickness of the polarizer 1 may be 2 μm or more, 4 μm or more, or 5 μm or more. The thickness of the polarizer 1 may be 7 to 12 μm, and in some cases may be 1 to 7 μm, particularly 4 to 6 μm. In this specification, a polarizer 1 having a thickness of 10 μm or less may be called a thin polarizer. A thin polarizer tends to have less thickness unevenness and excellent visibility. Furthermore, a thin polarizer has the advantage that dimensional change is suppressed and it has excellent durability. The thin polarizer allows the polarizing film 10 to be made thinner. When the polarizer 1 is a thin polarizer, it is necessary to adjust the iodine concentration in the polarizer 1 to be high so that the polarizing film 10 has a polarization degree sufficient for practical use. In the polarizing film 10 of the present embodiment, even when the polarizer 1 has a small thickness and the iodine concentration in the polarizer 1 is high, the transmission of iodine from the polarizer 1 to the outside can be sufficiently suppressed.

[0054] The polarizer 1 can be produced by, for example, dyeing a hydrophilic polymer film such as a polyvinyl alcohol-based film by immersing it in an aqueous solution of iodine, and stretching it to 3 to 7 times its original length. The hydrophilic polymer film may be immersed in an aqueous solution containing boric acid, potassium iodide, etc., as necessary. Furthermore, the hydrophilic polymer film may be immersed in water and washed before dyeing, as necessary. By washing the hydrophilic polymer film with water, dirt and antiblocking agents attached to the surface can be washed off. Washing the hydrophilic polymer film with water causes the hydrophilic polymer film to swell, which has the effect of suppressing unevenness in dyeing. The hydrophilic polymer film may be stretched after dyeing with iodine, may be stretched while dyeing, or may be stretched before dyeing with iodine. The hydrophilic polymer film may be stretched in an aqueous solution containing boric acid, potassium iodide, etc., or in water.

[0055] Representative examples of thin polarizers include those described in JP 51-069644 A, JP 2000-338329 A, WO 2010 / 100917 A, JP 2014-59328 A, and JP 2012-73563 A. These thin polarizers can be produced by a production method including a step of stretching a laminate including a polyvinyl alcohol-based resin (PVA-based resin) layer and a resin substrate for stretching, and a step of dyeing the obtained stretched film. In this production method, since the PVA-based resin layer is supported by the resin substrate for stretching, defects such as breakage due to stretching are unlikely to occur.

[0056] From the viewpoint of being able to stretch at a high ratio and improving the polarization performance, the thin polarizer is preferably produced by a manufacturing method including a stretching step in an aqueous boric acid solution among the above manufacturing methods, and particularly preferably produced by a manufacturing method including a step of performing auxiliary in-air stretching before the stretching step in an aqueous boric acid solution. Manufacturing methods including a stretching step in an aqueous boric acid solution are disclosed in International Publication No. 2010 / 100917, JP 2014-59328 A, JP 2012-73563 A, etc. Manufacturing methods including a step of performing in-air stretching are disclosed in JP 2014-59328 A, JP 2012-73563 A, etc.

[0057] [Resin layer] The resin layer 2 and the polymer P contained in the resin layer 2 are not particularly limited, as long as the polymer P has a structural unit derived from a (meth)acrylic acid ester and further has a value of y1 calculated by the above formula (1) or a value of y2 calculated by the above formula (2) of less than 1.3.

[0058] The (meth)acrylic acid ester may be a monofunctional (meth)acrylic acid ester having one (meth)acryloyl group, or may be a polyfunctional (meth)acrylic acid ester having two or more (meth)acryloyl groups. The polymer P preferably contains a structural unit derived from a polyfunctional (meth)acrylic acid ester. The polymer P containing a structural unit derived from a polyfunctional (meth)acrylic acid ester tends to be able to further suppress the migration of iodine from the polarizer 1 to the resin layer 2. The number of (meth)acryloyl groups contained in the polyfunctional (meth)acrylic acid ester is not particularly limited, and is, for example, 2 to 6, and preferably 2 to 4. When the number of (meth)acryloyl groups contained in the polyfunctional (meth)acrylic acid ester is too large, unreacted (meth)acryloyl groups may remain in the polymer P.

[0059] The number of carbon atoms in the portion other than the (meth)acryloyl group in the (meth)acrylic acid ester (hereinafter sometimes referred to as the ester portion) is not particularly limited, and is, for example, 1 to 18, and preferably 4 to 10. The ester portion may contain a ring structure. The ring structure may contain a heteroatom such as a nitrogen atom or an oxygen atom, but is preferably composed only of alicyclic hydrocarbons. The ring structure may be a condensed ring structure such as tricyclodecane, or a single ring structure such as cyclohexane. Furthermore, the ring structure may be a lactone ring. The ester portion may contain a functional group such as an ether group.

[0060] The (meth)acrylic acid ester may contain a polar group, but preferably does not contain a polar group. In this specification, the polar group means a group containing a bond between a hydrogen atom and a heteroatom such as an oxygen atom or a nitrogen atom. Examples of the polar group include a hydroxyl group, a carboxyl group, a primary amine group, and a secondary amine group.

[0061] Examples of (meth)acrylic acid esters include dicyclopentanyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, lauryl (meth)acrylate, 5-(meth)acryloxy-2,6-norbornane carbolactone, 3,3,5-trimethylcyclohexyl (meth)acrylate, 4-t-butylphenyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 2-isopropyl-2-adamantyl (meth)acrylate, 4-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, 1-anthracene (meth)acrylate, 1-anthracene methyl ... monofunctional (meth)acrylic acid esters such as dimethylol-tricyclodecane di(meth)acrylate, 1,3-adamantanediol di(meth)acrylate, 1,3,5-adamantantriol-1,5-di(meth)acrylate, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, etc.; trifunctional (meth)acrylic acid esters such as trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, 1,3,5-adamantantriol tri(meth)acrylate, etc.; tetrafunctional (meth)acrylic acid esters such as pentaerythritol tetra(meth)acrylate, etc.; and hexafunctional (meth)acrylic acid esters such as dipentaerythritol hexa(meth)acrylate, etc.

[0062] The polymer P preferably contains structural units derived from (meth)acrylic acid esters as a main component, and preferably consists essentially of structural units derived from (meth)acrylic acid esters. In this specification, "main component" means a structural unit contained most abundantly in the polymer P on a weight basis. The content of structural units derived from (meth)acrylic acid esters in the polymer P is, for example, 50% by weight or more, preferably higher than 70% by weight, more preferably 80% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and particularly preferably 99% by weight or more.

[0063] The polymer P may further contain a structural unit derived from a radical polymerizable monomer other than the (meth)acrylic acid ester, or a structural unit derived from an anionically polymerizable monomer other than the (meth)acrylic acid ester, and may further contain a structural unit derived from a cationically polymerizable monomer.

[0064] Examples of other radical polymerizable monomers other than (meth)acrylic acid esters include styrene-based compounds. The styrene-based compounds include, for example, an aromatic ring and one or more vinyl groups. As with (meth)acrylic acid esters, the styrene-based compounds may include a polar group, but preferably do not include a polar group. Examples of the styrene-based compounds include styrene, α-methylstyrene, vinylbenzyl chloride, butoxystyrene, and vinylpyridine.

[0065] Examples of the cationic polymerizable monomer include vinyl ether compounds, epoxy compounds, and oxetane compounds. Examples of the vinyl ether compounds include aliphatic vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether, and cyclohexyl vinyl ether; aromatic vinyl ethers such as phenyl vinyl ether, 2-phenoxyethyl vinyl ether, and p-methoxyphenyl vinyl ether; and polyfunctional vinyl ethers such as butanediol-1,4-divinyl ether, triethylene glycol divinyl ether, and dipropylene glycol divinyl ether.

[0066] Examples of the epoxy compound include aromatic epoxy compounds, alicyclic epoxy compounds, and aliphatic epoxy compounds. Examples of the aromatic epoxy compound include bisphenol A, Bisphenol F , diglycidyl ether compounds of bisphenols such as bisphenol S (bisphenol type epoxy resins); novolac type epoxy resins such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; and glycidyl ether compounds of polyalcohols such as tetrahydroxyphenylmethane, tetrahydroxybenzophenone, and polyvinylphenol.

[0067] Examples of alicyclic epoxy compounds include vinylcyclohexene dioxide, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, limonene dioxide, bis(3,4-epoxycyclohexylmethyl)adipate, dicyclopentadiene diepoxide, bicyclononadiene diepoxide, tricyclopentadiene diepoxide, dodecahydro-2,6-methano-2H-oxirano[3',4']cyclopenta[1',2':6,7]naphth[2,3-b]oxirane, and the like.

[0068] Examples of the aliphatic epoxy compound include 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, and polyethylene glycol diglycidyl ether.

[0069] Examples of the oxetane compound include 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, bis[(3-ethyl-3-oxetanyl)methyl]ether, and 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane.

[0070] The polymer P preferably contains a structural unit derived from a polyfunctional monomer. Examples of the polyfunctional monomer include the above-mentioned polyfunctional (meth)acrylic acid ester, polyfunctional vinyl ether compound, polyfunctional epoxy compound, and polyfunctional oxetane compound. The content of the structural unit derived from the polyfunctional monomer in the polymer P is, for example, 20% by weight or more, preferably 40% by weight or more, more preferably 50% by weight or more, and may be 70% by weight or more in some cases. The upper limit of the content of the structural unit derived from the polyfunctional monomer is not particularly limited, and is, for example, 95% by weight.

[0071] The polymer P may contain a structural unit derived from a monomer having a polar group, but preferably does not contain one. When the polymer P contains a structural unit derived from a monomer having a polar group, iodine contained in the polarizer 1 tends to easily approach the resin layer 2. Therefore, the content of the structural unit derived from a monomer having a polar group in the polymer P is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, and particularly preferably 2% by weight or less.

[0072] The resin layer 2 contains, for example, a polymer P as a main component. The content of the polymer P in the resin layer 2 is, for example, 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more. The resin layer 2 preferably consists essentially of the polymer P. However, the resin layer 2 may contain additives other than the polymer P, such as an antistatic agent, an antioxidant, inorganic particles, and a leveling agent.

[0073] The thickness of the resin layer 2 is not particularly limited and is, for example, 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. From the viewpoint of sufficiently suppressing the transmission of iodine contained in the polarizer 1 to the outside, the thickness of the resin layer 2 is preferably 0.3 μm or more, and may be 0.5 μm or more.

[0074] The resin layer 2 may be attached to the polarizer 1 via an adhesive layer or an easy-adhesion layer. Examples of the adhesive layer for attaching the resin layer 2 to the polarizer 1 include those exemplified for the adhesive layer 3 described later. The easy-adhesion layer can be formed of a resin containing a polymer having, for example, a polyester skeleton, a polyether skeleton, a polycarbonate skeleton, a polyurethane skeleton, a silicone skeleton, a polyamide skeleton, a polyimide skeleton, a polyvinyl alcohol skeleton, or the like. The polymer contained in the resin may be one type or two or more types. The easy-adhesion layer may contain an additive. Examples of the additive include a tackifier, an ultraviolet absorber, an antioxidant, a stabilizer such as a heat stabilizer, and the like. The thickness of the easy-adhesion layer is not particularly limited and is preferably 0.01 to 5 μm, more preferably 0.02 to 2 μm, and further preferably 0.05 to 1 μm. The easy-adhesion layer may be a laminate of a plurality of layers.

[0075] [Adhesive layer] The adhesive layer 3 is a layer containing an adhesive. The material of the adhesive is not particularly limited, and known materials can be used. Examples of the adhesive contained in the adhesive layer 3 include water-based adhesives and active energy ray curing adhesives. Examples of the active energy ray curing adhesives that can be used include those disclosed in JP 2019-147865 A and JP 2016-177248 A.

[0076] The thickness of the adhesive layer 3 is not particularly limited and is, for example, 3.0 μm or less, preferably 0.01 to 3.0 μm, more preferably 0.1 to 2.5 μm, and further preferably 0.5 to 1.5 μm. If the thickness of the adhesive layer 3 is too small, the cohesive force of the adhesive layer 3 may be insufficient, and the peeling force may decrease. If the thickness of the adhesive layer 3 is too large, peeling may occur at the adhesive layer 3 when stress is applied to the cross section of the polarizing film 10. That is, peeling failure may occur in the polarizing film 10 due to impact.

[0077] [Transparent protective film] The transparent protective film 4 is preferably excellent in transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc. Examples of materials for the transparent protective film 4 include polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose; (meth)acrylic polymers such as polymethyl methacrylate; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymers (AS resins); polycarbonate-based polymers; olefin-based polymers such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic olefin-based polymers such as polynorbornene; vinyl chloride-based polymers; amide-based polymers such as nylon and aromatic polyamide; imide-based polymers; sulfone-based polymers; polyethersulfone-based polymers; polyetheretherketone-based polymers; polyphenylene sulfide-based polymers; vinyl alcohol-based polymers; vinylidene chloride-based polymers; vinyl butyral-based polymers; arylate-based polymers; polyoxymethylene-based polymers; epoxy-based polymers; and mixtures of these polymers.

[0078] Of the above-mentioned polymers, the transparent protective film 4 preferably contains a polymer that functions as a thermoplastic resin. The content of the thermoplastic resin in the transparent protective film 4 is preferably 50% by weight to 100% by weight, more preferably 50% by weight to 99% by weight, even more preferably 60% by weight to 98% by weight, and particularly preferably 70% by weight to 97% by weight. If the content of the thermoplastic resin in the transparent protective film 4 is less than 50% by weight, the inherent functions of the thermoplastic resin, such as high transparency, may not be fully exhibited.

[0079] The transparent protective film may contain one or more additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, color inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0080] The transparent protective film 4 may be a polymer film described in JP 2001-343529 A, WO 01 / 37007, etc. Examples of materials for this polymer film include a resin composition containing a thermoplastic resin having a substituted and / or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted and / or unsubstituted phenyl group and a nitrile group in the side chain. A specific example of this polymer film is a film formed from a resin composition containing an alternating copolymer of isobutylene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. This film is obtained, for example, by mixing and extruding the resin composition. This film has a small phase difference and a small photoelastic coefficient, so that defects such as unevenness due to distortion of the polarizing film 10 can be eliminated. Furthermore, this film has a small moisture permeability, so it has excellent durability in a humid environment.

[0081] The moisture permeability of the transparent protective film 4 is not particularly limited, but is preferably 150 g / m 2 / 24h or less is preferable. In this case, the intrusion of moisture in the air into the polarizing film 10 can be suppressed, and the change in moisture content of the polarizing film 10 can be suppressed. This can suppress the occurrence of curling and dimensional changes in the polarizing film 10 during storage, etc. Examples of materials for forming the transparent protective film 4 with low moisture permeability include polyester-based polymers, polycarbonate-based polymers, arylate-based polymers, amide-based polymers, olefin-based polymers, cyclic olefin-based polymers, (meth)acrylic polymers, and mixtures thereof. Examples of materials for forming the transparent protective film 4 include polycarbonate-based polymers, cyclic olefin-based polymers, and (meth)acrylic polymers, and particularly preferably cyclic olefin-based polymers and (meth)acrylic polymers.

[0082] The thickness of the transparent protective film 4 is not particularly limited, but from the viewpoints of strength, handleability, and the like, it is preferably 5 to 100 μm, more preferably 10 to 60 μm, and even more preferably 13 to 40 μm.

[0083] The surface of the transparent protective film 4 may be subjected to an easy-adhesion treatment such as a corona treatment or a plasma treatment in order to improve the adhesion between members. An easy-adhesion layer may be disposed on the surface of the transparent protective film 4. As the easy-adhesion layer, those described above for the resin layer 2 can be used.

[0084] [Adhesive layer] The adhesive layer 5 is a layer containing an adhesive. The material of the adhesive is not particularly limited, and for example, a material containing a (meth)acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like as a base polymer can be used. In particular, an acrylic adhesive containing a (meth)acrylic polymer is suitable as a material for the adhesive layer 5 because it has excellent optical transparency, appropriate adhesive properties such as wettability, cohesiveness, and adhesiveness, and excellent weather resistance, heat resistance, and the like.

[0085] The pressure-sensitive adhesive layer 5 may be a laminate of multiple layers having different compositions. The thickness of the pressure-sensitive adhesive layer 5 is appropriately determined depending on the purpose of use, adhesive strength, etc., and is, for example, 1 to 500 μm, preferably 1 to 200 μm, and more preferably 1 to 100 μm. The thickness of the pressure-sensitive adhesive layer 5 may be 50 μm or less.

[0086] Before the polarizing film 10 is laminated to the image display panel, the pressure-sensitive adhesive layer 5 may be laminated with a separator. The separator can prevent contamination of the pressure-sensitive adhesive layer 5. As the separator, for example, a thin film such as a plastic film, a rubber sheet, paper, a cloth, a nonwoven fabric, a net, a foam sheet, a metal foil, or a laminate thereof, which is coated with a release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide release agent, as necessary, can be used.

[0087] [Other parts] The polarizing film 10 may further include other members in addition to the above-mentioned members. The polarizing film 10 may further include, for example, a transparent substrate located on the viewing side of the resin layer 2. The transparent substrate may be located on the outermost side of the polarizing film 10. The transparent substrate is made of, for example, glass or a polymer. Examples of polymers constituting the transparent substrate include polyethylene terephthalate, polycycloolefin, and polycarbonate. The transparent substrate made of glass has a thickness of, for example, 0.1 mm to 1 mm. The transparent substrate made of a polymer has a thickness of, for example, 10 μm to 200 μm.

[0088] The transparent substrate is bonded to the resin layer 2 via, for example, an OCA (optical clear adhesive) layer. As the OCA layer, for example, the above-mentioned adhesive layer 5 can be used. The thickness of the OCA layer is preferably 150 μm or less.

[0089] The polarizing film 10 may further include an optical film such as a reflector, an anti-transmitting plate, a retardation film, a viewing angle compensation film, or a brightness enhancement film. The retardation film includes, for example, a half-wave plate or a quarter-wave plate. In the polarizing film 10, the retardation film may be disposed closer to the image display panel than the polarizer 1 (for example, between the pressure-sensitive adhesive layer 5 and the transparent protective film 4), or may be disposed closer to the viewing side than the polarizer 1.

[0090] The polarizing film 10 may further include a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. In the polarizing film 10, the hard coat layer may be disposed on the viewing side with respect to the resin layer 2.

[0091] [Method of manufacturing polarizing film] The method for producing the polarizing film 10 is not particularly limited, and includes, for example, a step of polymerizing a monomer M having a value of y1 calculated by the above formula (1) of less than 1.3 to obtain a polymer P. The method for producing the polarizing film 10 may include, instead of the above step, a step of polymerizing a monomer M having a value of y2 calculated by the above formula (2) of less than 1.3 to obtain a polymer P. In detail, the polarizing film 10 can be produced by the following method. First, the polarizer 1 and the transparent protective film 4 are bonded together via the adhesive layer 3. Next, a coating liquid containing the above monomer M and a polymerization initiator is prepared. The polymerization initiator can be appropriately selected depending on the monomer M contained in the coating liquid. The polymerization initiator is preferably a photopolymerization initiator. When the coating liquid contains a cationic polymerizable monomer, a photoacid generator can also be used as the polymerization initiator.

[0092] Examples of the photopolymerization initiator include benzophenone-based compounds such as benzil, benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone; aromatic ketone compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and α-hydroxycyclohexylphenyl ketone; acetophenone-based compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropan-1-one; benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; Benzoin ether compounds such as benzoin butyl ether and anisoin methyl ether; aromatic ketal compounds such as benzil dimethyl ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenone-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; camphorquinone; halogenated ketones; acylphosphinoxides; and acylphosphonates.

[0093] Examples of the photoacid generator include compounds represented by the following formula (i). L + X - (i)

[0094] In formula (i), L + is an onium cation, and X - PF6 - , SbF6 - , AsF6 - , SbCl6 - , BiCl5 -, SnCl6 - , ClO4 - , dithiocarbamate anion and SCN - The counter anion is selected from the group consisting of:

[0095] Specific examples of photoacid generators include "CYRACURE UVI-6992" and "CYRACURE UVI-6974" (both manufactured by Dow Chemical Japan Co., Ltd.), "ADEKA OPTOMER SP150", "ADEKA OPTOMER SP152", "ADEKA OPTOMER SP170", and "ADEKA OPTOMER SP172" (all manufactured by ADEKA Corporation), "IRGACURE250" (manufactured by Chiba Specialty Chemicals Co., Ltd.), "CI-5102", "CI-2855" (both manufactured by Nippon Soda Co., Ltd.), and "SAN-AID SI-60L ", "Sanaid SI-80L", "Sanaid SI-100L", "Sanaid SI-110L", "Sanaid SI-180L" (all manufactured by Sanshin Chemical Industry Co., Ltd.), "CPI-100P", "CPI-100A" (all manufactured by San-Apro Ltd.), "WPI-069", "WPI-113", "WPI-116", "WPI-041", "WPI-044", "WPI-054", "WPI-055", "WPAG-281", "WPAG-567", and "WPAG-596" (all manufactured by Wako Pure Chemical Industries, Ltd.).

[0096] The content of the polymerization initiator in the coating liquid is, for example, 20% by weight or less, preferably 0.01 to 20% by weight, more preferably 0.05 to 10% by weight, and further preferably 0.1 to 5% by weight.

[0097] Next, the coating liquid is applied onto the polarizer 1. This allows a film (coating) containing the monomer M and a polymerization initiator to be formed on the polarizer 1. Next, the monomer M is polymerized so that the resin layer 2 is formed from the coating. The polymerization of the monomer M can be performed by a known method. For example, when a photopolymerization initiator or a photoacid generator is used as the polymerization initiator, the monomer M can be polymerized by irradiating the coating with active energy rays. Examples of active energy rays include visible light and ultraviolet light. In this specification, the resin layer 2 produced by polymerizing the monomer M contained in the coating may be referred to as a cured resin layer. Next, the pressure-sensitive adhesive layer 5 is attached to the transparent protective film 4 to obtain the polarizing film 10.

[0098] The resin layer 2 may be prepared by the following method. First, a monomer M is polymerized to obtain a polymer P. The obtained polymer P is added to a solvent to prepare a coating liquid. Examples of the solvent include organic solvents capable of dissolving or dispersing the polymer P. Next, the coating liquid is applied onto the polarizer 1 to prepare a coating film. The coating film is dried to obtain the resin layer 2.

[0099] [Characteristics of polarizing film] In the polarizing film 10 of the present embodiment, the transmission of iodine contained in the polarizer 1 to the outside is sufficiently suppressed in a high-temperature and high-humidity environment. That is, the concentration of iodine in the polarizer 1 hardly changes in a high-temperature and high-humidity environment. The change in the concentration of iodine in the polarizer 1 can be read, for example, from the change in the single transmittance of the polarizing film 10. As an example, when the polarizing film 10 is placed in an atmosphere of 65°C and 90% RH for 24 hours in a state where the polarizing film 10 is attached to non-alkali glass via the adhesive layer 5, the change ΔY1 in the single transmittance of the polarizing film 10 is, for example, 5 or less, preferably 4 or less, more preferably 2 or less, even more preferably 1.5 or less, and particularly preferably 1 or less.

[0100] Specifically, the change in single transmittance ΔY1 can be measured by the following method. First, the single transmittance Ts1 of the laminate obtained by bonding the polarizing film 10 to non-alkali glass via the adhesive layer 5 is measured. Next, this laminate is placed in an atmosphere of 65°C and 90% RH for 24 hours. The single transmittance Ts2 of the laminate after being placed in this atmosphere is measured. The value obtained by subtracting the single transmittance Ts1 from the single transmittance Ts2 is regarded as the change in single transmittance ΔY1. The single transmittance of the laminate is the Y value corrected for luminosity using a 2-degree visual field (C light source) according to JIS Z8701-1999. The single transmittance can be measured using a commercially available spectrophotometer such as DOT-3 manufactured by Murakami Color Research Laboratory. The measurement wavelength for the single transmittance is 380 to 700 nm (at 10 nm intervals). The alkali-free glass is glass that does not substantially contain an alkali component (alkali metal oxide), and more specifically, the weight ratio of the alkali component in the glass is, for example, 1000 ppm or less, and further 500 ppm or less. The alkali-free glass is, for example, in a plate shape and has a thickness of 0.5 mm or more.

[0101] The single transmittance Ts1 is not particularly limited and is, for example, 42% to 46%, preferably 43% or more, and more preferably 44% or more. The single transmittance Ts2 is not particularly limited and is, for example, 42% to 48%, preferably 47% or less, and more preferably 46% or less.

[0102] (Modification of Polarizing Film) In the polarizing film 10, the resin layer 2 may be located closer to the image display panel side than the polarizer 1, which will be described later. As shown in FIG. 2, in the polarizing film 11 according to this modification, the resin layer 2 is located closer to the image display panel side than the polarizer 1. Except for the position of the resin layer 2, the structure of the polarizing film 11 is the same as the structure of the polarizing film 10. Therefore, the same reference symbols are used for elements common to the polarizing film 10 and the polarizing film 11 of the modification, and their explanations may be omitted. That is, the explanations of the following embodiments are mutually applicable unless there is a technical contradiction. The following embodiments may be combined with each other unless there is a technical contradiction.

[0103] The resin layer 2 is, for example, located between the polarizer 1 and the adhesive layer 3, and is in direct contact with both the polarizer 1 and the adhesive layer 3. However, other layers such as an adhesive layer or an easy-adhesion layer may be located between the resin layer 2 and the polarizer 1. For example, the resin layer 2 may be bonded to the polarizer 1 via an adhesive layer or an easy-adhesion layer. Examples of the adhesive layer and the easy-adhesion layer for bonding the resin layer 2 to the polarizer 1 include those described above for the polarizing film 10. When the resin layer 2 is located closer to the image display panel than the polarizer 1, iodine contained in the polarizer 1 can be prevented from migrating to the adhesive layer 5 and permeating to the outside of the polarizing film 11 through the adhesive layer 5 in a high-temperature and high-humidity environment.

[0104] (Another variation of the polarizing film) The polarizing film 10 may further include other components in addition to the components described above. As shown in Fig. 3, the polarizing film 12 according to this modification further includes a transparent protective film (second transparent protective film) 6. Except for the second transparent protective film 6, the structure of the polarizing film 12 is the same as the structure of the polarizing film 10. Therefore, elements common to the polarizing film 10 and the polarizing film 12 of the modification are given the same reference symbols, and their explanation may be omitted.

[0105] The second transparent protective film 6 is located on the viewing side of the polarizer 1. The polarizer 1 is located, for example, between the first transparent protective film 4 and the second transparent protective film 6. The second transparent protective film 6 is located, for example, on the viewing side of the resin layer 2 and is located on the outermost side of the polarizing film 12. However, when the polarizing film 12 includes the above-mentioned transparent substrate, the second transparent protective film 6 may be located between the resin layer 2 and the transparent substrate. The second transparent protective film 6 is, for example, in direct contact with the resin layer 2. However, the second transparent protective film 6 may be bonded to the resin layer 2 via another layer such as an adhesive layer or a hard coat layer. Examples of the adhesive layer for bonding the second transparent protective film 6 to the resin layer 2 include those described above for the adhesive layer 3.

[0106] The second transparent protective film 6 can be the same as or different from the first transparent protective film 4. The first transparent protective film 4 and the second transparent protective film 6 may be the same as or different from each other.

[0107] In the polarizing film 12 provided with the second transparent protective film 6, the transmission of iodine contained in the polarizer 1 to the outside tends to be further suppressed in a high-temperature and high-humidity environment. As an example, when the polarizing film 12 is attached to non-alkali glass via the pressure-sensitive adhesive layer 5 and placed in an atmosphere of 65°C and 90% RH for 120 hours, the change ΔY2 in the single transmittance of the polarizing film 12 is, for example, 3 or less, preferably 2 or less, more preferably 1.5 or less, even more preferably 1 or less, and particularly preferably 0.8 or less.

[0108] Specifically, the change in single-piece transmittance ΔY2 can be measured by the following method. First, the single-piece transmittance Ts3 of the laminate obtained by bonding the polarizing film 12 to non-alkali glass via the adhesive layer 5 is measured. Next, this laminate is placed in an atmosphere of 65°C and 90% RH for 120 hours. After being placed in this atmosphere, the single-piece transmittance Ts4 of the laminate is measured. The value obtained by subtracting the single-piece transmittance Ts3 from the single-piece transmittance Ts4 is regarded as the change in single-piece transmittance ΔY2.

[0109] The single transmittance Ts3 is not particularly limited and is, for example, 42% to 46%, preferably 43% or more, and more preferably 44% or more. The single transmittance Ts4 is not particularly limited and is, for example, 42% to 48%, preferably 47% or less, and more preferably 46% or less.

[0110] (Yet another variation of the polarizing film) The polarizing film 10 may include two or more resin layers 2. As shown in Fig. 4, the polarizing film 13 according to this modified example includes two resin layers 2a and 2b. Except for the resin layer 2b, the structure of the polarizing film 13 is the same as the structure of the polarizing film 10. Therefore, elements common to the polarizing film 10 and the polarizing film 13 of the modified example are denoted by the same reference symbols, and their explanation may be omitted.

[0111] In the polarizing film 13, the polarizer 1 is located between two resin layers 2a and 2b. Specifically, the resin layer 2b is located closer to the image display panel than the polarizer 1 (for example, between the polarizer 1 and the adhesive layer 3). When the polarizer 1 is located between the two resin layers 2a and 2b, the polarizing film 13 tends to further suppress the transmission of iodine contained in the polarizer 1 to the outside.

[0112] The resin layer 2b may be in direct contact with the polarizer 1. However, other layers such as an adhesive layer or an easy-adhesion layer may be disposed between the resin layer 2b and the polarizer 1. For example, the resin layer 2b may be attached to the polarizer 1 via an adhesive layer or an easy-adhesion layer. Examples of the adhesive layer and easy-adhesion layer for attaching the resin layer 2b to the polarizer 1 include those described above for the polarizing film 10.

[0113] (Embodiment of Image Display Device) As shown in Fig. 5, the image display device 100 of the present embodiment includes a polarizing film 10 and an image display panel 20. In the image display device 100, polarizing films 11, 12, or 13 can also be used instead of the polarizing film 10. In the image display device 100, the polarizing film 10 is bonded to the image display panel 20 via, for example, an adhesive layer 5. Examples of the image display panel 20 include an organic EL display panel and a liquid crystal display panel, and an organic EL display panel is preferable.

[0114] The image display device 100 further includes, for example, an illumination system (not shown). As an example, the polarizing film 10, the image display panel 20, and the illumination system are arranged in this order, with the polarizing film 10 being located on the most visible side. The illumination system includes, for example, a backlight or a reflector, and irradiates the image display panel 20 with light. EXAMPLES

[0115] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.

[0116] <Thin polarizer> First, a laminate was prepared in which a PVA layer having a thickness of 9 μm was formed on an amorphous polyethylene terephthalate (PET) substrate. A stretched laminate was produced by performing an auxiliary air stretching at a stretching temperature of 130° C. on this laminate. Next, the stretched laminate was dyed using iodine to obtain a colored laminate. Furthermore, the colored laminate was stretched in an aqueous boric acid solution at a stretching temperature of 65° C. to obtain a laminate in which the amorphous PET substrate and the PVA layer were stretched together. In the laminate, the total stretching ratio was 5.94 times, and the thickness of the PVA layer was 5 μm. The PVA molecules of the PVA layer formed on the amorphous PET substrate by the above two-stage stretching were highly oriented. Furthermore, the iodine adsorbed by the dyeing was highly oriented in one direction as a polyiodine ion complex. The PVA layer included in the laminate functioned as a thin polarizer.

[0117] <Transparent protective film> First, a resin (imidized MS resin) composed of an imidized methyl methacrylate-styrene copolymer was prepared by the method described in Production Example 1 of JP 2010-284840 A. Then, 100 parts by weight of the imidized MS resin and 0.62 parts by weight of a triazine-based ultraviolet absorber (manufactured by Adeka Corporation, product name: T-712) were mixed at 220°C using a twin-screw kneader to prepare resin pellets. The obtained resin pellets were dried for 12 hours under an environment of 100.5 kPa and 100°C. Next, a film having a thickness of 160 μm was prepared by extruding the resin pellets from a T-die at a die temperature of 270°C using a single-screw extruder. Furthermore, this film was stretched in its conveying direction under an atmosphere of 150°C to adjust the thickness to 80 μm. Next, an easy-to-use adhesive containing a water-based urethane resin was applied to the film, and the film was stretched in a direction perpendicular to the conveying direction in an atmosphere of 150°C to obtain a transparent protective film having a thickness of 40 μm. The moisture permeability of this transparent protective film was 58 g / m 2 / 24h.

[0118] <Active energy ray-curable adhesive composition> 12 parts by weight of hydroxyethyl acrylamide (KJ Chemicals, trade name: HEAA), 24 parts by weight of 2-hydroxy-3-phenoxypropyl acrylate (Toagosei, trade name: ARONIX M-5700), 12 parts by weight of hydroxypivalic acid neopentyl glycol acrylic acid adduct (Kyoeisha Chemical, trade name: Light Acrylate HPP-A), 38 parts by weight of 1,9-nonanediol diacrylate (Kyoeisha Chemical, trade name: Light Acrylate 1,9ND-A), 10 parts by weight of acrylic oligomer (Toagosei, trade name: ARUFON UP-1190), 3 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (IGM Resins, trade name: OMNIRAD 907), and 2 parts by weight of 2,4-diethylthioxanthone (Nippon Kayaku, trade name: KAYACURE DETX-S) was mixed therein and stirred for 3 hours to obtain an active energy ray-curable adhesive composition.

[0119] <Laminate Comprising a Transparent Protective Film, an Adhesive Layer, and a Thin Polarizer> The active energy ray curable adhesive composition was applied to the bonding surface of the transparent protective film using an MCD coater (cell shape: honeycomb, gravure roll line count: 1000 rolls / inch, rotation speed 140% / to line speed) manufactured by Fuji Machinery Co., Ltd. The thickness of the coating film obtained was 0.7 μm. Next, the transparent protective film and the laminate including the PVA layer were bonded together using a rolling machine. At this time, the coating film and the PVA layer were brought into contact with each other. The line speed of the rolling machine was 25 m / min. Next, the obtained laminate was irradiated with active energy rays from the transparent protective film side. Visible light emitted from a visible light irradiation device (Light HAMMER10 manufactured by Fusion UV Systems) was used as the active energy rays. The light source of the visible light irradiation device was a gallium-filled metal halide lamp. In the visible light irradiation device, a V bulb was used as the bulb. The peak illuminance of the light emitted from the visible light irradiation device was 1600 mW / cm 2 In the wavelength range of 380 nm to 440 nm, the cumulative irradiation amount of the light emitted from the visible light irradiation device was 1000 mJ / cm 2 The illuminance of the light emitted from the visible light irradiation device was measured using a Sola-Check system manufactured by Solatell. The active energy ray curable adhesive composition in the coating film was cured by irradiating the laminate with active energy rays. Next, the laminate was dried with hot air at 70°C for 3 minutes to obtain a laminate a including a transparent protective film, an adhesive layer, and a thin polarizer.

[0120] [Example 1] (Polarizing film A) First, 50 parts by weight of dicyclopentanyl acrylate (manufactured by Hitachi Chemical Co., Ltd., trade name: Fancryl FA-513AS), 50 parts by weight of pentaerythritol tetraacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name: Light Acrylate PE-4A), 2 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (manufactured by IGM Resins, trade name: OMNIRAD 907), and 2 parts by weight of 2,4-diethylthioxanthone (manufactured by Nippon Kayaku Co., Ltd., trade name: KAYACURE DETX-S) were mixed to prepare a coating solution.

[0121] Next, the amorphous PET substrate adjacent to the PVA layer was removed from the laminate a. The above coating solution was applied onto the exposed PVA layer using a select roller #0 (manufactured by OSG System Products Co., Ltd.). The thickness of the resulting coating film was 1 μm. Next, the above-mentioned visible light irradiation device was used to irradiate the coating film with visible light under a nitrogen gas flow to polymerize the monomer. The coating film was cured by polymerization of the monomer, and a resin layer was formed.

[0122] Next, the surface of the transparent protective film was subjected to a corona treatment. A 20 μm thick adhesive layer was attached to this surface. The adhesive layer was made of an acrylic adhesive. This resulted in a polarizing film A having a resin layer, a polarizer, an adhesive layer, a transparent protective film, and an adhesive layer in this order.

[0123] (Polarizing film B) First, a coating solution was prepared by the same method as for polarizing film A. Using an MCD coater (cell shape: honeycomb, gravure roll line count: 700 rolls / inch, rotation speed 140% / to line speed) manufactured by Fujikikai Co., Ltd., the coating solution was applied to the bonding surface of a 20 μm-thick triacetyl cellulose (TAC) film. The thickness of the resulting coating film was 1 μm. Next, the amorphous PET substrate adjacent to the PVA layer was removed from the above-mentioned laminate a. Using a rolling machine, the TAC film and the laminate a were bonded together. At this time, the coating film and the PVA layer were brought into contact with each other. The line speed of the rolling machine was 25 m / min. Next, the resulting laminate was irradiated with active energy rays from the TAC film side. As the active energy rays, visible light emitted from the above-mentioned visible light irradiation device was used. By irradiating the laminate with active energy rays, the monomer in the coating film was polymerized. The coating film was hardened by the polymerization of the monomer. Next, the laminate was dried with hot air at 70° C. for 3 minutes. As a result, a resin layer was formed.

[0124] Next, the surface of the transparent protective film containing the imidized MS resin was subjected to a corona treatment. A 20 μm thick adhesive layer was attached to this surface. The adhesive layer was made of an acrylic adhesive. This resulted in a polarizing film B having a TAC film (second transparent protective film), a resin layer, a polarizer, an adhesive layer, a transparent protective film containing the imidized MS resin (first transparent protective film), and an adhesive layer in this order.

[0125] [Example 3-5, 7-16, Reference Example 1-2 , Comparative Examples 1, 3 and 5] Example 1 was prepared in the same manner as Example 1, except that the monomer contained in the coating solution for forming the resin layer was changed to the monomer shown in Table 1. 3-5, 7-16, Reference Example 1-2 Polarizing films A and B of Comparative Examples 1, 3 and 5 were prepared.

[0126] [Comparative Example 2] Polarizing films A and B of Comparative Example 2 were produced in the same manner as in Example 1, except that photocurable resin composition A was used as the coating liquid for forming the resin layer. The photocurable resin composition A was a mixture of 43 parts by weight of acryloylmorpholine (KJ Chemicals, trade name: ACMO), 29 parts by weight of 1,9-nonanediol diacrylate (Kyoeisha Chemical, trade name: Light Acrylate 1,9ND-A), 14 parts by weight of phenoxydiethylene glycol acrylate (Kyoeisha Chemical, trade name: Light Acrylate P2H-A), 10 parts by weight of acrylic oligomer (Toagosei, trade name: ARUFON UP-1190), 2 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (IGM Resins, trade name: OMNIRAD 907), and 2 parts by weight of 2,4-diethylthioxanthone (Nippon Kayaku, trade name: KAYACURE DETX-S).

[0127] [Comparative Example 4] Polarizing films A and B of Comparative Example 4 were produced in the same manner as in Example 1, except that photocurable resin composition B was used as the coating liquid for forming the resin layer. The photocurable resin composition B contained 12 parts by weight of hydroxyethyl acrylamide (manufactured by KJ Chemicals, trade name: HEAA), 20 parts by weight of 2-hydroxy-3-phenoxypropyl acrylate (manufactured by Toagosei, trade name: ARONIX M-5700), 12 parts by weight of hydroxypivalic acid neopentyl glycol acrylic acid adduct (manufactured by Kyoeisha Chemical, trade name: Light Acrylate HPP-A), 34 parts by weight of 1,9-nonanediol diacrylate (manufactured by Kyoeisha Chemical, trade name: Light Acrylate 1,9ND-A), 10 parts by weight of acrylic oligomer (manufactured by Toagosei, trade name: ARUFON UP-1190), 5 parts by weight of diethyl acrylamide (manufactured by KJ Chemicals, trade name: DEAA), 3 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (manufactured by IGM Resins, trade name: OMNIRAD The mixture was a mixture of 3 parts by weight of 2,4-diethylthioxanthone (manufactured by Nippon Kayaku Co., Ltd., trade name: KAYACURE DETX-S).

[0128] <Change in single unit transmittance ΔY1> For the polarizing film A of the examples and comparative examples, the change in the single transmittance ΔY1 was measured by the following method. First, the polarizing film A was attached to an alkali-free glass via an adhesive layer. The single transmittance Ts1 of the obtained laminate was measured. The single transmittance Ts1 was measured using a spectral transmittance meter with an integrating sphere (Dot-3c manufactured by Murakami Color Research Laboratory). Next, this laminate was placed in an atmosphere of 65°C and 90% RH for 24 hours. The single transmittance Ts2 of the laminate after being placed in this atmosphere was measured using the above-mentioned spectral transmittance meter. The change in the single transmittance ΔY1 was calculated by subtracting the single transmittance Ts1 from the single transmittance Ts2.

[0129] <Change in single unit transmittance ΔY2> For the polarizing film B of the examples and comparative examples, the change in the single transmittance ΔY2 was measured by the following method. First, the polarizing film B was attached to an alkali-free glass via an adhesive layer. The single transmittance Ts3 of the obtained laminate was measured. The single transmittance Ts3 was measured using a spectral transmittance meter with an integrating sphere (Dot-3c manufactured by Murakami Color Research Laboratory). Next, this laminate was placed in an atmosphere of 65°C and 90% RH for 120 hours. The single transmittance Ts4 of the laminate after being placed in this atmosphere was measured using the above-mentioned spectral transmittance meter. The change in the single transmittance ΔY2 was calculated by subtracting the single transmittance Ts3 from the single transmittance Ts4.

[0130] <Value of y1 calculated by formula (1)> The values ​​of x1 to x3 of the monomers contained in the coating liquid for forming the resin layer used in the examples and comparative examples were specified by the above-mentioned method. The number of rotatable bonds and the number of reaction points contained in the monomer were calculated using Dragon (version 7.0). The polarization term ΔP (MPa 1 / 2 ) was calculated using HSPiP (version 5). Furthermore, the value of y1 was calculated based on the formula (1) using the values ​​of x1 to x3.

[0131] <Value of y2 calculated by formula (2)> The values ​​of x1 to x5 of the monomers contained in the coating liquid for forming the resin layer used in the examples and comparative examples were specified by the above-mentioned method. The number of rotatable bonds and the number of reaction points contained in the monomers were calculated using Dragon (version 7.0). The polarization term ΔP (MPa 1 / 2 ) was calculated using HSPiP (version 5). Materials Studio (BIOVIA, ver. 8.0.0.843) and WebMO (ver. 19.0.009e) were used to calculate the charge of each atom constituting the monomer and the x component of the dipole moment. Furthermore, the value of y2 was calculated based on formula (2) using the values ​​of x1 to x5.

[0132] <Tensile storage modulus E1 and E2> The tensile storage moduli E1 and E2 of the resin layers used in the examples and comparative examples were measured by the above-mentioned method. As the dynamic viscoelasticity measuring device, a dynamic viscoelasticity measuring device RSA-G2 manufactured by TA Instruments was used.

[0133] <Linear expansion coefficients α1 and α2> The linear expansion coefficients α1 and α2 of the resin layers used in the examples and comparative examples were measured by the above-mentioned method. The thermomechanical analyzer TMA 4000 SE manufactured by Netzsch was used as the thermomechanical analyzer.

[0134] <Dipole moment D> The dipole moment D of the monomer contained in the coating liquid for forming the resin layer used in the examples and comparative examples was calculated by the above-mentioned method. The dipole moment D was calculated using Materials Studio (manufactured by BIOVIA, ver. 8.0.0.843) and WebMO (ver. 19.0.009e).

[0135] [Table 1]

[0136] The abbreviations in Table 1 are as follows. FA513AS: dicyclopentanyl acrylate, Hitachi Chemical TMP-A: Trimethylolpropane triacrylate, manufactured by Kyoeisha Chemical Co., Ltd. TBCHA: 4-t-butylcyclohexyl acrylate, manufactured by KJ Chemicals DCP-A: Dimethylol-tricyclodecane diacrylate, manufactured by Kyoeisha Chemical Co., Ltd. GBLA: γ-butyrolactone acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd. ACMO: acryloylmorpholine, KJ Chemicals PE-4A: Pentaerythritol tetraacrylate, manufactured by Kyoeisha Chemical Co., Ltd. DPE-6A: Dipentaerythritol hexaacrylate, manufactured by Kyoeisha Chemical Co., Ltd. 1,9ND-A: 1,9-nonanediol diacrylate, manufactured by Kyoeisha Chemical Co., Ltd. 9EG-A: Polyethylene glycol #400 diacrylate, manufactured by Kyoeisha Chemical Co., Ltd.

[0137] As can be seen from Table 1, in the polarizing film A of the embodiment in which the value of y1 calculated by formula (1) or the value of y2 calculated by formula (2) is less than 1.3, the change in the single transmittance ΔY1 is 5 or less, and the transmission of iodine to the outside in a hot and humid environment is sufficiently suppressed. Similarly, in the polarizing film B of the embodiment, the change in the single transmittance ΔY2 is 3 or less, and the transmission of iodine to the outside in a hot and humid environment is sufficiently suppressed. On the other hand, in the polarizing films A and B of the comparative example in which the values ​​of y1 and y2 are 1.3 or more, the change in the single transmittance is larger than that of the embodiment, and the transmission of iodine to the outside in a hot and humid environment cannot be sufficiently suppressed.

[0138] Furthermore, the values ​​of x1 to x5, y1 and y2 were determined by the above-mentioned method for the monomers contained in the active energy ray curable resin compositions used in Examples 1-4 and Comparative Example 1 of Patent Document 1. These active energy ray curable resin compositions contained only epoxy compounds as monomers and did not contain (meth)acrylic acid esters. The calculated values ​​of y1 and y2 could not adequately predict the properties of the cured layer of the active energy ray curable resin composition. From this, it can be seen that y1 calculated by formula (1) and y2 calculated by formula (2) are particularly suitable as indicators for predicting the properties of a resin layer containing a polymer having a structural unit derived from a (meth)acrylic acid ester. [Industrial Applicability]

[0139] The polarizing film of the present invention can be suitably used for, for example, mobile displays such as mobile phones, smartphones, and notebook computers; and in-vehicle displays such as panels for car navigation devices, cluster panels, and mirror displays.

Claims

1. a polarizer including iodine; a resin layer including a polymer having a structural unit derived from a monofunctional (meth)acrylic acid ester and a structural unit derived from a polyfunctional (meth)acrylic acid ester; a dipole moment D of a monomer for forming the polymer is 2 Debye or less; y calculated by the following formula (1) 1 A polarizing film having a value of less than 1.

3. y 1 =(0.279)x 1 +(-1.51)x 2 +(0.178)x 3 +0.386 (1) In the formula (1), x 1 is the number of rotatable bonds contained in the monomer for forming the polymer, x 2 is the number of reaction sites contained in the monomer for forming the polymer, x 3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ).

2. The y 1 The polarizing film according to claim 1 , wherein the value of is 0.5 or less.

3. 3. The polarizing film according to claim 1, wherein at least one of the following requirements (i) to (iv) is satisfied: (i) The tensile storage modulus E1 of the resin layer at 65° C. in water is 1×10 8 Pa or more. (ii) The tensile storage modulus E2 of the resin layer at 85° C. in water is 1×10 8 Pa or more. (iii) The linear expansion coefficient α1 of the resin layer when the resin layer is heated from 25° C. to 65° C. and the measurement atmosphere is humidified from 10% RH to 90% RH is 400×10 -6 / K or less. (iv) The linear expansion coefficient α2 of the resin layer when the resin layer is heated from 25° C. to 85° C. and the measurement atmosphere is humidified from 10% RH to 85% RH is 300×10 -6 / K or less.

4. The polarizing film according to any one of claims 1 to 3, wherein in the polymer, a total content of the structural units derived from the monofunctional (meth)acrylic acid ester and a content of the structural units derived from the polyfunctional (meth)acrylic acid ester is higher than 70% by weight.

5. 5. The polarizing film according to claim 1, wherein the content of structural units derived from polyfunctional monomers in the polymer is 20% by weight or more.

6. 6. The polarizing film according to claim 1, wherein the content of structural units derived from monomers having a polar group in the polymer is 20% by weight or less.

7. The polarizing film according to any one of claims 1 to 6, wherein the resin layer is located on a viewing side relative to the polarizer.

8. The polarizing film according to any one of claims 1 to 7, wherein the resin layer is in direct contact with the polarizer.

9. The resin layer is provided with two layers. The polarizing film according to any one of claims 1 to 6, wherein the polarizer is located between two of the resin layers.

10. Further comprising an adhesive layer and a first transparent protective film, The polarizing film according to any one of claims 1 to 9, wherein the polarizer, the adhesive layer, and the first transparent protective film are arranged in this order in a stacking direction.

11. Further comprising a second transparent protective film; The polarizing film of claim 10 , wherein the polarizer is located between the first transparent protective film and the second transparent protective film.

12. Further comprising an adhesive layer, The polarizing film according to any one of claims 1 to 11, wherein the polarizer is located on a viewing side of the pressure-sensitive adhesive layer.

13. The polarizing film according to any one of claims 1 to 12, An image display panel; An image display device comprising:

14. A method for producing a polarizing film including an iodine-containing polarizer and a resin layer including a polymer having a structural unit derived from a monofunctional (meth)acrylic acid ester and a structural unit derived from a polyfunctional (meth)acrylic acid ester, comprising: The manufacturing method includes: y calculated by the following formula (1) 1 to obtain the polymer, The method for producing a polarizing film, wherein the dipole moment D of the monomer is 2 Debye or less. y 1 =(0.279)x 1 +(-1.51)x 2 +(0.178)x 3 +0.386 (1) In the formula (1), x 1 is the number of rotatable bonds contained in the monomer, x 2 is the number of reactive sites contained in the monomer, x 3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer 1 / 2 ).

15. The method further includes forming a film containing the monomer and the polymerization initiator on the polarizer, The method of claim 14, further comprising polymerizing the monomer so as to form the resin layer from the film.

16. the polymerization initiator is a photopolymerization initiator, The method according to claim 15 , wherein the monomer is polymerized by irradiating the film with active energy rays.

17. a polarizer including iodine; a resin layer including a polymer having a structural unit derived from a monofunctional (meth)acrylic acid ester and a structural unit derived from a polyfunctional (meth)acrylic acid ester; a dipole moment D of a monomer for forming the polymer is 2 Debye or less; y calculated by the following formula (2) 2 A polarizing film having a value of less than 1.

3. y 2 =(0.255)x 1 +(-1.57)x 2 +(0.151)x 3 +(-18.0)x 4 +(0.0987)x 5 +(-8.26) (2) In the formula (2), x 1 is the number of rotatable bonds contained in the monomer for forming the polymer, x 2 is the number of reaction sites contained in the monomer for forming the polymer, x 3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ) and x 4 is the charge (C) of the most negatively charged atom among the atoms that function as hydrogen bond acceptors in the monomer for forming the polymer, x 5 is the x-component (Debye) of the dipole moment calculated by molecular simulation using the software "Materials Studio" for the monomer for forming the polymer.

18. A method for producing a polarizing film including an iodine-containing polarizer and a resin layer including a polymer having a structural unit derived from a monofunctional (meth)acrylic acid ester and a structural unit derived from a polyfunctional (meth)acrylic acid ester, comprising: The manufacturing method includes: y calculated by the following formula (2) 2 to obtain the polymer, The method for producing a polarizing film, wherein the dipole moment D of the monomer is 2 Debye or less. y 2 =(0.255)x 1 +(-1.57)x 2 +(0.151)x 3 +(-18.0)x 4 +(0.0987)x 5 +(-8.26) (2) In the formula (2), x 1 is the number of rotatable bonds contained in the monomer for forming the polymer, x 2 is the number of reaction sites contained in the monomer for forming the polymer, x 3 is the polarization term δP (MPa) in the Hansen solubility parameter of the monomer for forming the polymer 1 / 2 ) and x 4 is the charge (C) of the most negatively charged atom among the atoms that function as hydrogen bond acceptors in the monomer for forming the polymer, x 5 is the x-component (Debye) of the dipole moment calculated by molecular simulation using the software "Materials Studio" for the monomer for forming the polymer.

Citation Information

Patent Citations

  • Curable adhesive composition and polarizing plate using the same

    JP2016153474A

  • Polarizing plate with adhesive layer and manufacturing method of the same, active energy ray curable polymer composition used for the manufacture, and liquid crystal display

    JP2017075986A

  • Optical laminate

    JP2018169512A

  • Optical film, method for producing same, polarizing plate and liquid crystal display device

    WO2014119487A1

  • Laminated optical film and method for manufacturing same, and image display device

    WO2019058778A1